Is there an urgency in hydratic cyst of the lung? - Delbene, Roberto; Maglione, Oscar; Salom, Andrés; Volpi, Mauricio; Muniz, Gustavo (Cirugía del Uruguay, 2000)
The rupture of a pulmonary hydatid cyst [HCJ may cause a secondary hydatidosis [local, bronchial seeding, secondary pleural]. Consequently the classical view was that an afflicted pulmonary HC constituted a surgical urgency.